Too much R&D?: vertical differentiation in a model of monopolistic competition - Jan Kranich (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
This paper discusses a model of vertical and horizontal product differentiation within the Dixit-Stiglitz framework of monopolistic competition. Firms compete not only in prices and horizontal attributes of their products, but also in the quality that can be controlled by R&D activities. Based upon the results of a general equilibrium model, intra-sectoral trade and the welfare implications of public intervention in terms of research promotion are considered. The analysis involves a numerical application to ten basic European industries
Keywords: D43; F12; L13; L16; 330; Innovationswettbewerb; Produktdifferenzierung; Monopolistischer Wettbewerb; Interindustrielle Verflechtung; Forschungs- und Technologiepolitik; Wohlfahrtseffekt; Industrielle Forschung; Theorie; EU-Staaten